Perspectives of Agricultural Students at the University for Development Studies on Farming as a Livelihood in Ghana - Quansah, Joseph Yaw Dwamena; Osei, Samuel; Abudu, Amadu Musah (Advances in Social Sciences Research Journal, 2024)
The study aims to examine the perceptions of agriculture students in a Ghanaian University regarding farming as a sustainable livelihood after graduation. This study is grounded in the structuration theory. The target respondents for the study consisted of 105 final-year agriculture students from the Faculty of Agriculture. A total of 83 students were considered for the sample size which was determined using the Yamane (1967) sample size determination formula. The study adopted a descriptive survey design, anchored in the positivist paradigm. The study used a structured questionnaire for data collection. Descriptive statistics were employed for data analysis. The results revealed that a significant proportion of the students (46.1%) resided in rural areas where agriculture is the primary livelihood activity. Also, the study revealed that about 38.2% of the participants expressed willingness to grow food crops for their livelihood. The findings of the study further revealed that working in an educational institution (Mean= 3.0) was the most preferred livelihood option among participants. The study revealed that the major challenge deterring participants from pursuing farming as a sustainable livelihood is a lack of initial capital to start farming, with 67.1% of participants indicating this as a demotivating factor. The study recommended that government and other stakeholders should provide the necessary incentives in agriculture to arouse students’ interest in taking up agriculture-related careers after graduation as a means of livelihood in Ghana.